Identification of unique and common low abundance tumour-specific transcripts by suppression subtractive hybridization and oligonucleotide probe array analysis - Liu, B H; Goh, C H K; Ooi, L L P J; Hui, K M (Oncogene, 2008)
Most human cancers are characterized by genetic aberrations accompanied by altered expression and function of numerous genes. Applying genome-wide, microarray gene expression analysis to identify deregulated genes in different tumour types can provide potential gene candidates as diagnostic and prognostic tools and promising targets for drug development. However, the detection of deregulated genes with low levels of expression remains a major challenge. In this study, we have designed a strategy, termed modified suppression subtractive hybridization (mSSH), to identify genes encoding rare transcripts. The strategy entails incorporating the T 7 -promoter sequence at the 5′ end of the noncoding cDNA strand during first strand cDNA synthesis to generate unidirectional antisense RNA from the resultant cDNA following conventional SSH. These transcripts are subsequently analysed by Affymetrix oligonucleotide gene arrays. Here, we have used five hepatocellular carcinoma (HCC), five breast carcinoma and four nasopharyngeal carcinoma (NPC) biopsies separately as testers and their corresponding normal biopsies as drivers to enrich for low abundance tumour type-specific transcripts. The total detectable number of probe sets following mSSH was reduced almost 10-fold in comparison to those detected for the same resected tumour tissues without undergoing subtraction, thus yielding a subtraction efficacy of over 90%. Using this experimental approach, we have identified 48 HCC-specific, 45 breast carcinoma-specific, and 83 NPC-specific genes. In addition, 115 genes were upregulated in all the three cancer types. When compared to gene-profiling data obtained without mSSH, the majority of these identified transcripts were of low abundance in the original cancer tissues. mSSH can therefore serve as a comprehensive molecular strategy for pursuing functional genomic studies of human cancers.